2014
DOI: 10.3819/ccbr.2014.90003
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Genetics of Vocal Learning

Abstract: Language is a complex communicative behavior unique to humans, and its genetic basis is poorly understood. Genes associated with human speech and language disorders provide some insights, originating with the FOXP2 transcription factor, a mutation in which is the source of an inherited form of developmental verbal dyspraxia. Subsequently, targets of FOXP2 regulation have been associated with speech and language disorders, along with other genes. Here, we review these recent findings that implicate genetic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 175 publications
(249 reference statements)
1
23
0
Order By: Relevance
“…Based on the expression patterns of various regulatory genes and staining for acetylcholinesterase, Abellán and Medina () have suggested that the StC–ITCv complex may represent the avian counterpart of the rodent intercalated nuclei (ITC) of the amygdala which are important for fear extinction (Likhtik, Popa, Apergis‐Schoute, Fidacaro, & Paré, ; Mańko, Geracitano, & Capogna, ). Interestingly, Vicario et al () recently demonstrated that both StC and ITCv in zebra finches were rich in FoxP2, a transcription factor important for song learning and maintenance (Condro & White, ; Heston & White, ; Murugan, Harward, Scharff, & Mooney, ; Scharff & Haesler, ; Wohlgemuth, Adam, & Scharff, ) as well as language learning in humans (Lai, Fisher, Hurst, Vargha‐Khadem, & Monaco, ; reviewed in French & Fisher, ). Further studies on the expression and role of FoxP2 in StC and ITCv, their connections and functions are warranted in house crows, since they are also highly social birds, whose vocalizations may have a learned component and almost certainly, a social component as well.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression patterns of various regulatory genes and staining for acetylcholinesterase, Abellán and Medina () have suggested that the StC–ITCv complex may represent the avian counterpart of the rodent intercalated nuclei (ITC) of the amygdala which are important for fear extinction (Likhtik, Popa, Apergis‐Schoute, Fidacaro, & Paré, ; Mańko, Geracitano, & Capogna, ). Interestingly, Vicario et al () recently demonstrated that both StC and ITCv in zebra finches were rich in FoxP2, a transcription factor important for song learning and maintenance (Condro & White, ; Heston & White, ; Murugan, Harward, Scharff, & Mooney, ; Scharff & Haesler, ; Wohlgemuth, Adam, & Scharff, ) as well as language learning in humans (Lai, Fisher, Hurst, Vargha‐Khadem, & Monaco, ; reviewed in French & Fisher, ). Further studies on the expression and role of FoxP2 in StC and ITCv, their connections and functions are warranted in house crows, since they are also highly social birds, whose vocalizations may have a learned component and almost certainly, a social component as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in animal models support this hypothesis. CNTNAP2 [Condro & White, ] is important for song mimicking in birds, which is a process that is highly dependent on motor control. In addition, recent studies in individuals with dyslexia have reported associations between sequence variations in CNTNAP2 and stuttering [Petrin et al, ] as well as difficulties with motor‐heavy tasks such as rapid oral reading [Peter et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we investigated the expression of FoxP2 in the different components of the extended amygdala, since alterations in the gene encoding this transcription factor have been associated with language learning deficits in humans (Lai et al 2001; Haesler et al 2007; reviewed by Fisher and Scharff 2009, Fischer and Hammerschmidt 2011, and French and Fisher 2014), and may contribute (not alone, but combination with other genes) to the development of autism (Park et al 2014), which implies not only deficits in communication but also in social skills (Bacon and Rappold 2012). Songbirds like the zebra finch are excellent models for studying the role of FoxP2 in the brain, since learned songs are used for social communication, and this transcription factor is regulated by singing and in fact required for proper song learning and song maintenance (Scharff and Haesler 2005; Wohlgemuth et al 2014; Murugan et al 2013; Condro and White 2014; Heston and White 2015). In mice, FoxP2 is expressed in the extended amygdala, including the intercalated amygdalar cells and the medial amygdala (Campbell et al 2009; Kaoru et al 2010), but, other than that, the exact location of the expression within this mosaic-like complex structure is unknown.…”
Section: Introductionmentioning
confidence: 99%